Tree - Jose, Francisco Sionil 1924- (Manila Solidaridad Publishing House, 1997)
Tree is a story of a boy growing up in a small Ilokano town, surrounded by friends below his social class, by relatives and doting servants who have served his family all their lives. It is also a story of oppression and compassion. Tree belongs to Francisco Sionil Jose's largest body of work known as the Rosales novels. Like much of his fiction, it depicts man's continuing and often futile search for justice and a moral order.
Winner [of] The 1980 Ramon Magsaysay Award for journalism, literature and creative communication arts.
Keywords: Philippine fiction (English).; History -- Fiction